1999
DOI: 10.1016/s0144-8617(98)00123-4
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterisation of sago starch

Abstract: The physico-chemical characteristics of various sago starch samples from South East Asia were determined and compared to starches from other sources. X-ray diffraction studies showed that all the sago starches exhibited a C-type diffraction pattern. Scanning electron microscopy showed that they consist of oval granules with an average diameter around 30 mm. Proximate composition studies showed that the moisture content in the sago samples varied between 10.6% and 20.0%, ash between 0.06% and 0.43%, crude fat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
2
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(147 citation statements)
references
References 29 publications
(31 reference statements)
15
126
2
4
Order By: Relevance
“…The physicochemical properties of sago starch shown in Table 4 have been shown to depend on the specie and the time of harvest [150]. Sago starch consists of oval granules with an average size of 30 mm and the XRD studies showed that sago starches exhibited C-type diffraction pattern [149].…”
Section: Sago Palm (Metroxylon Spp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical properties of sago starch shown in Table 4 have been shown to depend on the specie and the time of harvest [150]. Sago starch consists of oval granules with an average size of 30 mm and the XRD studies showed that sago starches exhibited C-type diffraction pattern [149].…”
Section: Sago Palm (Metroxylon Spp)mentioning
confidence: 99%
“…Sago starch consists of oval granules with an average size of 30 mm and the XRD studies showed that sago starches exhibited C-type diffraction pattern [149]. Sago starch has an AM content of 24-31% and the gelatinization temperature of 69.4-70.18C [150].…”
Section: Sago Palm (Metroxylon Spp)mentioning
confidence: 99%
“…The transition temperature of the sago starch film exhibited a sharp endothermic peak at 238 °C indicating film degradation temperature due to the chitosan portion (td). The characteristic temperature of the starches depends on the morphology and degree of crystallinity within the starch molecule (Ahmad et al, 1999). With the glycerol incorporation into the sago starch-chitosan films, the DSC thermograms illustrated a broad endothermic peak at 165 to 280 °C corresponding to the degradation temperature of 182.2 °C of the glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…a Determined using the polyelectrolyte titration method (Kam and Gregory, 1999). b Determined using one point method (Ahmad et al, 1999). c Determined using element analysis method (Lin et al, 2012).…”
Section: Cationic Starch Modified Soilsmentioning
confidence: 99%